Critical Thinking, Critical Reading, and Multiple Intelligences: Impact of Parenting Style in Education - Miranti Eka Putri; Muhammad Ilyas; Zaka Hadikusuma Ramadan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Intellectual intelligence is not the only main focus of education but it is also the ability to think critically and read critically as a key element in preparing future generations. This research aims to investigate the impact of parenting styles on the development of children’s critical thinking, critical reading, and multiple intelligences in the educational context. The data collection techniques used were interviews and observation. The research data validity used source and technical triangulations. The research participants were elementary to middle school-level children who came from different parenting styles. Democratic parenting style appears as a strong factor to influence the development of children's critical thinking and critical reading skills. Parents who open the discussions, provide encouragement to question information, and provide space for exploration against the ideas at home, are positively correlated with higher levels of children's critical thinking. In the context of multiple intelligences, a democratic parenting style is also proven to play a key role. This research also provides limitations, especially in terms of the generalization of findings because it uses a case study design with a limited sample.